Dynamic restructuring of Cu-doped SnS2 nanoflowers for highly selective electrochemical CO2 reduction to formate - Chen, Mengxin (2022)
With ever-increasing energy consumption and continuous rise in atmospheric CO2 concentration, electrochemical reduction of CO2 into chemicals/fuels is becoming a promising yet challenging solution. Sn-based materials are identified as attractive electrocatalysts for the CO2 reduction reaction (CO2 RR) to formate but suffer from insufficient selectivity and activity, especially at large cathodic current densities. Herein, we demonstrate that Cu-doped SnS2 nanoflowers can undergo in situ dynamic restructuring to generate catalytically active S-doped Cu/Sn alloy for highly selective electrochemical CO2 RR to formate over a wide potential window. Theoretical thermodynamic analysis of reaction energetics indicates that the optimal electronic structure of the Sn active site can be regulated by both S-doping and Cu-alloying to favor formate formation, while the CO and H2 pathways will be suppressed. Our findings provide a rational strategy for electronic modulation of metal active site(s) for the design of active and selective electrocatalysts towards CO2 RR.